(untitled) (EAAE Annual Conference Proceedings, 2019)
This paper is the result of multiple forms of inquiry on architectural education across the sixteen schools of architecture part of the Nordic Baltic Academy of Architecture NBAA. In particular it reports the following: — Fourteen in-depth conversations conducted with architectural students during October, November, December 2018, and January 2019 across eleven schools of architecture part of the NBAA: KADK in Copenhagen, Chalmers in Gothenburg, AHO in Oslo, BAS in Bergen, VGTU in Vilnius, VDA in Vilnius, RTU in Riga, EKA in Tallinn, Aalto in Helsinki, NTNU in Trondheim, and IUA Iceland University of the Arts in Reykjavik. — A workshop on architectural education with the second-year students in architecture conducted at the IUA. — A reflection based on a questionnaire posed to all second-year students at the IUA (architecture, fashion, visual communication, and product) and international students who came to Iceland to participate to the multidisciplinary six-week live project called ‘Together 2019 a Platform for Citizenship Design’.